Analysis the Role of Headmaster in Applying Quality of Education in Primary School District, Aceh Barat - Musdiani Musdiani; Mardhatillah Mardhatillah; Khausar Khausar (BIRCU, 2019)
The aim of this Research is to find out the headmaster's role in implementing quality education management in primary school (SDN) Gunung Keling, Meureubo district, Aceh Barat Regency, to find out what constraints the principal faces in implementing quality management of education in primary school (SDN) Gunung Keling, Meureubo district, Aceh Barat regency. The study used a qualitative approach. This type of Research is descriptive (descriptive research). Research time is on August 8 to 27, 2018. His data collection techniques such as: observation methods, interview methods and documentation methods. The research data to be analyzed in this study is the role of the headmaster in implementing education quality management in primary school of Gunung Keling, Meureubo district, Aceh Barat regency, namely: the role of the headmaster as Educator, Manager, Administrator, Supervisor, Leader and Motivator. What obstacles faced by headmaster in implementing education quality management in primary school of Gunung Keling, Meureubo district, Aceh Barat regency, seen from the results of the study are: to overcome the obstacles to improving teacher quality carried out is to continuously carry out communication and educational quality culture campaigns for teachers who are still low on awareness and in overcoming the lack of teaching staff for permanent subjects, the school requests teachers to work through the Aceh Barat district Education Office.